Job satisfaction and organizational commitment on employee performance in the Regional Office of the Ministry of Law in North Maluku Province - Trisliatanto, Dimas Agung; Marasabessy, Zainal Abidin; Iryanto, Muhammad; Lobubun, Ridwan; Fatmona, Haryati (Technium Social Sciences Journal, 2026)
This study aimed to examine the effect of job satisfaction and organizational commitment on employee performance at the Regional Office of the Ministry of Law in North Maluku Province. The objects of this study were employees at the Regional Office of the Ministry of Law in North Maluku Province. The research method employed was a quantitative approach, utilizing cross-sectional data and involving 89 respondents. The research instrument had been tested for validity and reliability, showing that all items are valid and reliable. Data were collected using a questionnaire, distributed to employees working at the Regional Office of the Ministry of Law in North Maluku Province. Multiple linear regression analysis was used to test the research hypothesis with the SPSS application. The results of this study suggested that job satisfaction had no significant effect on performance, whereas organizational commitment had a positive effect on employee performance. Job satisfaction and organizational commitment affected employee performance simultaneously. This finding confirms that increasing organizational commitment is a dominant factor in driving employee performance improvements, while job satisfaction is not a significant predictor in the context of this study. However, job satisfaction and organizational commitment will have a significant effect if tested simultaneously on employee performance.